PENGARUH PENGALAMAN USAHA, STRATEGI DIVERSIFIKASI, DAN PENGGUNAAN E-COMMERCE TERHADAP PENGGUNAAN INFORMASI AKUNTANSI - Gabriela Rosellini Wisnu Geraldin; Baldric Siregar; Frasto Biyanto; Miswanto, Miswanto (Bajang Institute, 2025)
This study aims to examine whether business experience, product diversification strategy, and use of e-commerce influence the use of accounting information. The population of this research is all MSMEs in Yogyakarta City. The sampling method in this research is purposive sampling technique. The sample in this study were 96 UMKM registered on the Yogyakarta City E-UMKM platform and the Nglarisi Yogyakarta City platform. Data analysis methods used in this research are descriptive statistics, data quality testing, and hypothesis testing. The results of this study indicate that business experience, product diversification strategy, and use of e-commerce have a significant positive effect on the use of accounting information